Prevalence and demographic correlates of online grocery shopping: results from a nationally representative survey during the COVID-19 pandemic. Issue 11 (19th November 2022) - Duffy, Emily W; Lo, Amy; Hall, Marissa G; Taillie, Lindsey Smith; Ng, Shu Wen
Abstract: Objective: To estimate the prevalence of online grocery shopping in a nationally representative sample and describe demographic correlates with online grocery shopping. Design: The Nielsen COVID-19 Shopper Behavior Survey was administered to a subset of Nielsen National Consumer Panel participants in July 2020. We used survey weighted-multivariable logistic regression to examine demographic correlates of having ever online grocery shopped. Setting: Online survey. Participants: 18 598 Nielsen National Consumer Panel participants in the USA. Results: Thirty-nine percent of respondents had purchased groceries online, and among prior purchasers, 89 % indicated that they would continue to online grocery shop in the next month. Canned/packaged foods were the most shopped for grocery category online, followed by beverages, fresh foods and lastly frozen foods. In adjusted analyses, younger respondents (39 years or less) were more likely (47 %) to have ever shopped for groceries online than older age groups (40–54 years, 55–64 years and 65+ years) (29 %, 22 % and 23 %, respectively, all P < 0·001). Those with greater than a college degree were more likely to have ever grocery shopped online (45 %) than respondents with some college education (39 %) and with a high school education or less (32 %) (both P < 0·001). Having children, having a higher income and experiencing food insecurity, particularly among higher income food-insecure households, were also associated with a higher probability of prior online grocery shopping. Conclusions: The COVID-19 pandemic accelerated the transition to online grocery shopping. Future research should explore the nutrition implications of online grocery shopping.